1993
DOI: 10.1007/bf01429185
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of cobalt clusters with deuterium

Abstract: The kinetics of chemical reactions of cobalt clusters Con with deuterium are described. Absolute rate constants have been measured in the size range n = 7-68 at 293 K. The rate constants are found to be a strong function of cluster size, varying by a factor of 400. This size dependence is most prominent for n = 7 to 25:Co15 is the most reactive cluster, and Co7-9 and Co19-20 are particularly unreactive. Abrupt changes in the rate constants from one cluster size to the next are observed. For the clusters above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Ho et al 35,36 have studied the gas phase reaction and saturated absorption on the surface of neutral cobalt clusters Co m (m = 7-68), and found a similar D 2 reactivity dependence on cluster size for the cluster sizes reported by Smalley and co-workers. Absolute rate constants and reaction probabilities were also determined, and temperature dependence of the rate constants for dissociative adsorption of the first D 2 molecule to cobalt clusters Co m (m = 9-21) was examined over the temperature range of 133-373 K. 35,36 The rate constants for clusters m = 10-13, 15-17 show no dependence on temperature, indicating that D 2 chemisorption reaction has no activation barrier. The rate constants for Co 9 and Co 14 increase at higher temperatures, which suggest the presence of activation barriers (8.8 and 7.8 kJ/mol, respectively).…”
Section: Introductionsupporting
confidence: 52%
“…Ho et al 35,36 have studied the gas phase reaction and saturated absorption on the surface of neutral cobalt clusters Co m (m = 7-68), and found a similar D 2 reactivity dependence on cluster size for the cluster sizes reported by Smalley and co-workers. Absolute rate constants and reaction probabilities were also determined, and temperature dependence of the rate constants for dissociative adsorption of the first D 2 molecule to cobalt clusters Co m (m = 9-21) was examined over the temperature range of 133-373 K. 35,36 The rate constants for clusters m = 10-13, 15-17 show no dependence on temperature, indicating that D 2 chemisorption reaction has no activation barrier. The rate constants for Co 9 and Co 14 increase at higher temperatures, which suggest the presence of activation barriers (8.8 and 7.8 kJ/mol, respectively).…”
Section: Introductionsupporting
confidence: 52%
“…Metal–hydrogen cluster reactivity has been extensively studied with a focus on iron, , cobalt, ,,, vanadium, and niobium. A typical example in Figure illustrates the reactivity of cationic Fe n + and V n + clusters with hydrogen (D 2 was used in order to avoid mass degeneracy). , It was found that the presence of positive charge had a substantial influence on the reaction rate for the majority of iron and vanadium clusters, ,, and the kinetics of D 2 chemisorption on Fe n + /V n + clusters exhibited a nonmonotonic dependence on n . It is interesting to mention that studies of hydrogen chemisorption onto cationic Fe n + ( n = 4–22) found a generally enhanced (although size-selective) reactivity compared to that for neutral Fe n .…”
Section: Metal Cluster Reactivities With Nonpolar Moleculesmentioning
confidence: 99%
“…The rate constants at room temperature in a larger size range (n =7-68) have been presented earlier. 7 With the help of information about Co cluster geometry obtained from other experiments, these results can provide some insight into the details of the D2 dissociative adsorption on cobalt cluster surfaces.…”
Section: Introductionmentioning
confidence: 96%